Domestic violence treatment for abusive women: a treatment manual - Bowen, Ellen L. (Routledge, 2009)
Understanding domestic violence -- Theoretical foundations for treatment -- Effective treatment -- Diagnostic issues and categories -- Practice issues, cultural competence, ethical considerations -- Use of this therapy with other groups -- Before group : setting the stage for change to occur -- Record-keeping and administrative forms -- Facilitating the group : getting started -- Using binder handouts to facilitate growth and change